The Prevalence of Sedentary Habits Among International Students in Eastern Ukraine - A Cross-Sectional Study - Adebusoye, F.T.; Awuah, W.A.; Tenkorang, P.O.; et al. (American Journal of Lifestyle Medicine, 2023)
Objectives: To determine the occurrence of the behavioral risk factors associated with non communicable diseases among international undergraduate students. Methods: A cross-sectional study of 155 international undergraduate students originating from 13 different countries, was asked to complete a 26-question survey organized into 5 sections: demographics, physical activity, substance use, dietary habits, and health assessment. The online survey was distributed via social media platforms such as Viber, Telegram, WhatsApp, email, and Instagram. Results: The majority of surveyed students (86%) had good or excellent capacity for everyday activities, and 62.6% utilized their electronic gadgets for at least 8 h daily. 67.1% were regular consumers of junk food, and 53.5% did not get medical checkups. Students addicted to tobacco and/or cigarettes constituted 52.6% of the sample, 38.1% were regular alcohol consumers, and 97.4% reported being aware of the impact of substance use on their health. Conclusion: A significant number of students engage in unhealthy behaviors. Despite this, most students reported having good health, with only a small percentage engaging in regular physical activity. The prevalence of these unhealthy behaviors highlights
Research Article
Keywords: non-communicable diseases; sedentary behavior; dietary habits; physical inactivity